A feasibility study of the use of UmbiFlow™ to assess the impact of heat stress on fetoplacental blood flow in field studies - Bonell, A; Vannevel, V; Sonko, B; Mohammed, N; Vicedo-Cabrera, AM; Haines, A; Maxwell, NS; Hirst, J; Prentice, AM (Wiley, 2022)
Objective To evaluate the use of UmbiFlowTM in field settings to assess the impact of heat stress on umbilical artery resistance index (RI).